PEMANFAATAN LIMBAH LIGNOSELLULOSA UNTUK GAS BAKAR DENGAN METODE FERMENTASI - Tjutju Nurhayati Syahri (Jurnal Penelitian Hasil Hutan, 1990)
The gasification of  lignocellulosic waste  was conducted by fermentation method at  thermophilic condition  (45 -55°C).  The  material  was  obtained   from vegetable  market  at Bogor.  The gasification trial  made  in pilot  scale reactor  of having  capacity  of 30 m3 and equipped with gas holder of 50 m3, steam boiler of 50 kg/h and dual generator  of  17.5 kVA. The waste  was cut first become 1-3 cm  long on choper  of  0.3  m3/h  volume. Parameter  of  fermentation  choosed  on 10 m3  volume  actif  and  retention time  was 20.9 daysThe result revealed that  thermophilic fermentation of waste which had total solid about 22.3 % and ash about 33.9 % and  feeding about 478 kg fresh  waste per day produced   biogas about  28.7 m3 per day  on methane  content about 54.5 %, productivity  about 2.9 m3  per  m3  reactor per  day  and  efficiency  of  conversion  about 57  %.The total  of  fuel  consumption  along fermentation   per day was 4.34 hours of man hours  work  about  1.16 MJ and it was   from 1 tube  LPG  of  12.5 kg and  14.31 diesel. LPG  was used for  steam  boiler can  be changed  with  31.2 m3 biogas per  day. In  this  case the production of  biogas per day cannot be dropped for  the  total  of  fuel  consumption   even  steam boiler.  The  fermentation  of 22965  kg wet lignocellulosic   waste produced  gas bio about  1380 m3 and wet  residu for compos raw material  about  16430  kg. The  biogas production  was equavalent  with  44 LPG  container of  12.5 kg.